“Big Empty Negroes” and “Gay, Exciting” Mexicans: Recontextualizing Fellaheen Identities in Jack Kerouac’S On The Road - Mikelli, Eftychia (Miscelánea: A Journal of English and American Studies, 2012)
The term ‘Fellaheen’ is used in On the Road to collectively refer to marginalized ethnic groups. My article looks at constructions of Fellaheen identities in the novel, exploring representations of racial and gendered images in mainstream 1950s America. The article argues that the main characters’ perception of the Fellaheen is modelled upon the dissemination and reproduction of racialized and gendered stereotypes through dominant cultural practices in Cold War America. Addressing the biased discourses of his times, Kerouac explores their impact on individual, and by implication, national level, and ultimately questions their validity. Focusing on the novel’s preoccupation with African-American and Native American characters, I examine the textual strategies that problematize and ultimately expose the absurdity of the premises that condition the reproduction of standardized images of the exotic. Particularly focusing on an exploration of gender issues in the novel, I also address the processes of colonization that seem to be in operation, and subsequently explore strategies of narrative resistance in On the Road.
Keywords: Jack Kerouak; The Subterraneans; Fellaheen; Race; Gender